MELACAK ASAL TRADISI PENGUBURAN Dl GUA-GUA Dl KALIMANTAN - Sugiyanto, Bambang (Naditira Widya, 2009)
It is acknowledged that the indigenous people who inhabit Kalimantan are the Dayak. Ethnologists suggest that the Dayak are divided into hundreds of smaller ethnic groups. Each sub-ethnic group develops its particular burial tradition, either primary or secondary. Nevertheless, based on many ethno-archaeological researches, retained universal elements are indicated in each burial materialization among others is burial with or without container placed in caves or rock shelter. This article discusses the origins of cave burial tradition in Kalimantan.